Is Parent–Child Disagreement on Child Anxiety Explained by Differences in Measurement Properties? An Examination of Measurement Invariance Across Informants and Time - Olino, Thomas M.; Finsaas, Megan; Dougherty, Lea R.; Klein, Daniel N. (Frontiers in Psychology, 2018)
There are numerous empirical studies demonstrating that agreement between parent-reports of youth and youth self-reports of internalizing behavior problems is modest at best. This has spurred much research on factors that influence the magnitude of associations between informants, including individual difference characteristics of the informants and contexts through which individuals interact with the child. There is also tremendous interest in understanding symptom trajectories longitudinally. However, each of these lines of work are predicated on the assumptions that the psychometric construct that is being assessed from each informant and at each measurement occasion is the same. This study examined measurement invariance between maternal and child reports and longitudinally across ages nine and twelve on five dimensions of anxiety using the Screen for Child Anxiety and Related Disorders (SCARED; Birmaher, et al., 1999) . No cross-informant models for anxiety dimensions achieved acceptable fit and at least partial metric and scalar invariance. Moreover, few longitudinal models demonstrated acceptable fit and at least partial metric and scalar invariance. Thus, using the SCARED as an example, these results show that inter-informant agreement may be compromised by different item functioning, and highlight the need for testing invariance before using measures for longitudinal tracking of symptoms.